2017
DOI: 10.1073/pnas.1612943114
|View full text |Cite
|
Sign up to set email alerts
|

AMPA glutamate receptors are required for sensory-organ formation and morphogenesis in the basal chordate

Abstract: AMPA-type glutamate receptors (GluAs) mediate fast excitatory transmission in the vertebrate central nervous system (CNS), and their function has been extensively studied in the mature mammalian brain. However, GluA expression begins very early in developing embryos, suggesting that they may also have unidentified developmental roles. Here, we identify developmental roles for GluAs in the ascidian Ciona intestinalis. Mammals express Ca2+-permeable GluAs (Ca-P GluAs) and Ca2+-impermeable GluAs (Ca-I GluAs) by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 79 publications
(77 reference statements)
3
22
0
Order By: Relevance
“…Finally, we also observed that the touch response was not inhibited by perampanel (data not shown), despite the presence of VGLUTpositive epidermal sensory neurons [22]. This would appear to agree with the observation that primary RNs for the PNS, the eminens cells and the AMGs do not express the AMPAR ( [35]; and our observations). In addition to the AMPAR, the Ciona genome contains several other glutamate receptors including one kainate and one NMDA [34], although their expression has not been characterized.…”
Section: Parallel Visuomotor Circuitssupporting
confidence: 90%
See 2 more Smart Citations
“…Finally, we also observed that the touch response was not inhibited by perampanel (data not shown), despite the presence of VGLUTpositive epidermal sensory neurons [22]. This would appear to agree with the observation that primary RNs for the PNS, the eminens cells and the AMGs do not express the AMPAR ( [35]; and our observations). In addition to the AMPAR, the Ciona genome contains several other glutamate receptors including one kainate and one NMDA [34], although their expression has not been characterized.…”
Section: Parallel Visuomotor Circuitssupporting
confidence: 90%
“…Our results indicate that the PR-Is, with the exception of two cells, are glutamatergic, while the PR-IIs are a mixture of GABAergic and GABA/glutamatergic. The Ciona genome contains a single glutamate AMPA receptor (AMPAR) [34] that is expressed in larvae in the two antenna cells, and in a small cluster of neurons in the pBV [35]. Published results show that most of the pBV group of AMPAR-positive neurons are clustered at the ends of Arrestin-labeled photoreceptor axons, and that they extend their axons to the MG, suggesting they are photoreceptor RNs (see Figure 2B" in [35]).…”
Section: Parallel Visuomotor Circuitsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, GluAs are either Ca 2+ ‐permeable or ‐impermeable according to their subunit composition in mammals, while all GluAs are Ca 2+ ‐permeable in Ciona because they consist of only Q‐type subunits, which form Ca 2+ ‐permeable channels . Second, we found that GluAs are expressed in a limited subset of cells, including those in the photoreceptive anlage, during early development in Ciona , whereas they are expressed in most neurons in the mammalian CNS . Ascidian tadpoles have an otolith and ocellus to sense gravity and light, respectively.…”
Section: Introductionmentioning
confidence: 81%
“…On the other hand, Okamura et al estimated that only one GluA subunit is expressed in the ascidian Ciona , indicating that it is easier to artificially control GluAs in these organisms than in mammals. Taking advantage of the simplicity of ascidians as model animals, Hirai et al discovered the significance of GluAs in development (Figure ). Ascidians have a notochord and exhibit neural induction, and are therefore a prototype of vertebrate embryos .…”
Section: Introductionmentioning
confidence: 99%